RELIGIOUS MODERATION IN PLURAL SOCIETY : The Role of Muslim and Christian Youth in Instilling Attitude of Religious Moderation in Kudus - Khoirunnida , Firda; Amaliyah, Efa Ida (Journal of Islamic Studies and Civilization, 2025)
This study aims to reveal three things, namely the role of Muslim and Christian youth in instilling an attitude of religious moderation, the process of religious moderation , and what factors contribute to the occurrence of Religious Moderation in Gondangmanis Village, Bae, Kudus. This study is a field research and uses data collection techniques through observation of the situation of Kayuapu Hamlet and its community, interviews with Muslim and Christian youth and community leaders totaling 6 people , and documentation. The results of this study showed that: first , the role of Muslim and Christian youth in instilling religious moderation can be seen from their active participation in community organizations. With the youth's own initiative, they founded an interfaith organization called Popsika. Through Popsika, the activities of Muslim and Christian youth in social matters are covered. Second , the process of Kayuapu youth instilling religious moderation through action and dialogue, one of the youth's activities is conducting interfaith mutual assistance activities. Some of the youth's actions include providing security on major holidays for both Muslims and Christians, holding halal bihalal after Eid al-Fitr attended by Muslim and Christian youth, and carrying out charity for orphans and the poor in Kayuapu Hamlet. Third , factors influencing youth's moderate attitudes include parental teachings, environment, and self-awareness. Parental teachings or doctrines from an early age will influence a child's thinking and carry it into adulthood.